2022
DOI: 10.18549/pharmpract.2022.2.2678
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination, do women suffer from more side effects than men? A retrospective cross-sectional study

Abstract: The vaccine was the only way to fight against Coronavirus-19 (COVID-19) from its statement as a pandemic till day. COVID-19 vaccines were approved by the world health organization (WHO) in December 2020. Despite a large number of studies regarding the efficacy and safety of COVID-19 vaccines, to our knowledge, there were limited studies that outlined the gender disparity towards COVID-19 vaccine adverse effects. This study aims to outline the variety of side effects among men and women after getting COVID-19 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…The study results suggested that both females and males experienced side effects that mostly started within 8 hours after vaccination, lasted between one and three days, and were mainly limited to pain at the injection site, headache, fatigue, and fever, while serious side effects were rare. These results are consistent with what has been reported in the literature [ 27 , 28 ]. In this study, we also found that both females and males reported side effects to the vaccine over the three doses, but females showed more side effects that were between moderate and severe than their male counterparts.…”
Section: Discussionsupporting
confidence: 94%
“…The study results suggested that both females and males experienced side effects that mostly started within 8 hours after vaccination, lasted between one and three days, and were mainly limited to pain at the injection site, headache, fatigue, and fever, while serious side effects were rare. These results are consistent with what has been reported in the literature [ 27 , 28 ]. In this study, we also found that both females and males reported side effects to the vaccine over the three doses, but females showed more side effects that were between moderate and severe than their male counterparts.…”
Section: Discussionsupporting
confidence: 94%
“…The participants reported swelling, redness, and rashes, and females were found to be more affected than females. In this study, 77% of females and 65%males experienced side effects (18) likewise, our study females experienced more side effects than males.…”
Section: Discussionsupporting
confidence: 76%
“…There are many studies that demonstrate the variety of vaccine side effects based on gender [ 40 ]. The present study shows that females experienced more side effects compared with males [ 40 , 41 ], and the variation between males and females is attributed to sex hormones, including estrogen, progesterone, and testosterone, which can bind to the surface of immune cells and influence how they work. Exposure to estrogen causes immune cells to produce more antibodies in response to the vaccine in general [ 42 ].…”
Section: Discussionmentioning
confidence: 96%